1999
DOI: 10.5032/jae.1999.01038
|View full text |Cite
|
Sign up to set email alerts
|

Problems And Challenges Associated With The First Years Of Teaching Agriculture: A Framework For Preservice And Inservice Education

Abstract: This national study used the expertise of the winners of the NVATA Outstanding Young Member Award in identifying problems and challenges associated with the first years of teaching agriculture. The study was conducted using a three stage Delphi technique. The population surveyed were the state winners of the NVATA Outstanding Young Member Award for the years I995 and I996 and totaled 61 different names. The respondents to survey one listed over 350 problems and challenges associated with the first years of tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
73
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 1 publication
16
73
2
Order By: Relevance
“…However, many expressed uncertainty regarding their ability to relate their content knowledge and relevant personal experiences to their students in an effective manner consistent with previous findings (Anderson et al, 2012;Mundt & Connors, 1999). This indicates the importance of building a cognitive network in problem solving skills through strengthening the teachers' abilities to recall prior experiences and activate previous knowledge.…”
Section: Discussionsupporting
confidence: 75%
“…However, many expressed uncertainty regarding their ability to relate their content knowledge and relevant personal experiences to their students in an effective manner consistent with previous findings (Anderson et al, 2012;Mundt & Connors, 1999). This indicates the importance of building a cognitive network in problem solving skills through strengthening the teachers' abilities to recall prior experiences and activate previous knowledge.…”
Section: Discussionsupporting
confidence: 75%
“…Respondents were asked about their ability to "Manage work related stress" and "Balance priorities to make time for career and family/personal life" as examples. The four items of the WLB ability construct were derived from findings in other studies and encompassed work stress, time management, and work-life balance (Boone & Boone, 2007;Crutchfield et al, 2013;Edwards & Briers, 1999;Mundt & Connors, 1999;Murray et al, 2011;Myers et al, 2005;Torres et al, 2009;Walker et al, 2004). WLB achievement ability items were measured on a five-point scale which ranged from 1 "Very Low" to 5 "Very High."…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Although studies have found that agriculture teachers are not experiencing burnout (Croom, 2003), evidence suggests that they do experience overburdening workloads and stress (Boland, King, Williams, Duncan, & Ricketts, 2010;Boone & Boone, 2007;Edwards & Briers, 1998;Moore & Camp, 1979;Mundt & Connors, 1999;Myers et al, 2005;Newcomb et al, 1987;Talbert, Camp, & Heath-Camp, 1994;Torres et al, 2009). Furthermore, there exists a shortage of qualified teachers and attrition among agriculture teachers (Kantrovich, 2010).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…We developed the agricultural education competencies section of the instrument based on the Borich (1980) needs assessment model to assess the perceived ability and importance for each of the competencies. A list of 49 agricultural education competencies were developed from previous research (Boone & Boone, 2007;Duncan et al, 2006;Garton & Chung, 1996;Layfield & Dobbins, 2002;Mundt & Connors, 1999;Myers et al, 2005;Sorensen et al, 2005) and modified to meet the needs of agriculture teachers in Oregon. Teachers were asked to rate their perceived importance and perceived ability for each of the 49 competencies using a five-point Likert-type scale ranging from 1 "very low" to 5 "very high.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Numerous studies have been conducted within agricultural education to specifically identify the needs of beginning teachers, with some of those conducted as needs assessments (Edwards & Briers, 1999;Garton & Chung, 1996;Joerger, 2002;Layfield & Dobbins, 2002), others being direct assessments (Birkenholz & Harbstreit, 1987;Claycomb & Petty, 1983;Kahler, 1974;Miller & Scheid, 1982), Delphi panels (Mundt & Connors, 1999;Myers et al, 2005) or qualitative studies (Boone & Boone, 2007;Mundt, 1991;Talbert, Camp, & Heath-Camp, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%